2021
DOI: 10.2147/ndt.s317207
|View full text |Cite
|
Sign up to set email alerts
|

Ganoderic Acid A-Mediated Modulation of Microglial Polarization is Involved in Depressive-Like Behaviors and Neuroinflammation in a Rat Model of Post-Stroke Depression

Abstract: Background Post-stroke depression (PSD) is a common complication after stroke. Ganoderic acid A (GAA), one of the main bioactive Ganoderma triterpenoids, exerts preventive and therapeutic effects in many diseases. However, the function of GAA in PSD has not been well studied. Methods PSD model was established via stimulating rats with chronic unpredictable mild stress stimulations (CUMS) after middle cerebral artery occlusion (MCAO). Rats were treated with GAA before CU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…Moreover, inflammation is also involved in PSD development [ 68 , 69 ]. Considerable evidence indicates that inflammation is involved in the occurrence and development of PSD through related inflammatory pathways by producing inflammatory mediators [ 70 , 71 ].…”
Section: Ischemic Stroke and Depressionmentioning
confidence: 99%
“…Moreover, inflammation is also involved in PSD development [ 68 , 69 ]. Considerable evidence indicates that inflammation is involved in the occurrence and development of PSD through related inflammatory pathways by producing inflammatory mediators [ 70 , 71 ].…”
Section: Ischemic Stroke and Depressionmentioning
confidence: 99%
“…Moreover, emerging data have shown that plant-derived compounds can exert neuroprotective effects that prevent neurological disorders in depression. For instance, ganoderic acid A [ 227 ], asperosaponin VI [ 228 ], 20( S )-protopanaxadiol [ 229 ], scutellarin [ 230 ], astragalin [ 231 ], hesperidin [ 232 ], 5- O -methylvisammioside [ 233 ], ginkgolide B [ 234 ], leonurine [ 235 ], ferulic acid [ 236 ], and (+)-sesamin [ 69 ] were found to inactivate microglia in stress-induced depression models. Recent information concerning the antidepressant activity of phytochemicals through regulation of microglial polarization is illustrated in Table 2 .…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, microglial M1/M2 polarization plays important roles in mediating the balance between activation and suppression in inflammation ( Nakagawa and Chiba, 2014 ). Many studies have demonstrated that M1 (pro-inflammatory) polarization was related to depression ( Kalkman and Feuerbach, 2016 ; Zhang, L. et al, 2021 ). It needs more researches to explore whether these pathomechanisms are also relevant to PPD.…”
Section: Discussionmentioning
confidence: 99%